Northernmost record of Shepherd’s beaked whale (Tasmacetus shepherdi) – a morphological and genetic description from a stranding from Shark Bay, Western Australia. - Holyoake, Carly; Holley, David; Spencer, Peter; Salgado-Kent, Chandra; Coughran, Douglas; Lars, Bejder (Surrey Beatty and Sons, 2013)
Shepherd’s beaked whale (Tasmacetus shepherdi) is one of the least known cetaceans. Based on the location of 45 strandings and two at-sea sightings, T. shepherdi is thought to have a circumpolar distribution in the temperate waters of the Southern Hemisphere between latitudes 33°S and 50°S. On 10 November 2008, a female T. shepherdi was found dead on a beach in Shark Bay, Western Australia, at 113° 16’E, 26° 20’S. DNA sequencing was used to verify the identification of the specimen, which is the northern most record for this species. The age of the specimen was estimated to be between 12 and 15 years, based on counting dentine growth layer groups in two teeth, assuming an annual rate of deposition.